1998
DOI: 10.1103/physrevb.58.5329
|View full text |Cite
|
Sign up to set email alerts
|

Solidification and melting of mercury in a porous glass as studied by NMR and acoustic techniques

Abstract: The melting and freezing phase transitions of mercury in a porous glass were studied by NMR and acoustic techniques. The NMR measurements provided direct information on the total amount of liquid mercury versus temperature. A depression of the phase transition temperatures and pronounced hysteresis between melting and freezing were found. Acoustic measurements showed that the freezing process was irreversible while the melting process consisted of reversible and irreversible temperature ranges. The use of long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 52 publications
(82 reference statements)
2
28
0
Order By: Relevance
“…On a laboratory time scale liquids can be further supercooled below the thermodynamic freezing transition because of the presence of a kinetic barrier to crystallization ͑genuine and dynamical supercooling͒. [15][16][17][18] In homogeneous nucleation, this barrier can be reduced only through deep supercooling. It is well known, however, that bulk liquids cannot be supercooled below the particular temperatures where the thermal energy becomes comparable to the reduced kinetic barrier.…”
Section: B Pore-size Dependence Of Phase-transition Temperaturesmentioning
confidence: 99%
“…On a laboratory time scale liquids can be further supercooled below the thermodynamic freezing transition because of the presence of a kinetic barrier to crystallization ͑genuine and dynamical supercooling͒. [15][16][17][18] In homogeneous nucleation, this barrier can be reduced only through deep supercooling. It is well known, however, that bulk liquids cannot be supercooled below the particular temperatures where the thermal energy becomes comparable to the reduced kinetic barrier.…”
Section: B Pore-size Dependence Of Phase-transition Temperaturesmentioning
confidence: 99%
“…Due to high wetting ability it is possible to produce nanocomposite sodium nitrite on the basis of different porous media with various topology and dimensionality: 3D random dendritetype (porous glasses) and regular (opals) interconnected nanocaverns, quasi-1D parallel nanochannels (chrysotile asbestos and mobile crystalline material (MCM)-41) etc. Such nanocomposites have been extensively studied by different experimental methods including calorimetry [1], nuclear magnetic resonance (NMR) [2][3][4], ultrasonic [5,6] and dielectric [3,[7][8][9][10] measurements, Raman [11], X-ray and neutron diffraction [12][13][14][15] etc, and very intriguing and surprising results were obtained. In particular it was shown that sodium nitrite (NaNO 2 ) within artificial opals demonstrates a giant growth of ε (up to 10 8 at 100 Hz) at approaching the bulk melting temperature [7].…”
Section: Introductionmentioning
confidence: 99%
“…Significant melting point depression and large hysteresis between melting and freezing (solidification) have been observed for cryogenic fluids [1,5,6] and low melting point metals [7][8][9][10][11][12][13][14]. There are also reports [15,16] showing that nanoclusters consisting a few tens of atoms display much higher melting points than in the bulk form.…”
mentioning
confidence: 94%